Credible Influencers and Impulse Buying in Live-Streaming Commerce - Ginanjar Rahmawan; Indra Iryanto Nur Hidayat (Journal of Innovative and Creativity, 2026)
The purpose of this study was to examine the relationships among Influencer Credibility, Attitude Toward Influencers, and Impulse Buying within the context of live streaming commerce. As live streaming increasingly becomes an important digital marketing channel, understanding the psychological mechanisms that drive consumers’ spontaneous purchasing behavior is essential. This study specifically focuses on the role of influencer credibility in shaping consumer attitudes and triggering impulse buying decisions during live streaming interactions. This research employed a quantitative approach with an explanatory research design. Data were collected from individuals who had previously made purchases through live streaming commerce using an online questionnaire distributed via Google Forms. A purposive sampling technique was applied, resulting in 108 valid responses. The data were analyzed using Partial Least Squares. Structural Equation Modeling (PLS-SEM) with SmartPLS 3.2. Measurement validity and reliability were assessed through outer model analysis, while hypothesis testing and mediation analysis were conducted using inner model evaluation. The results indicate that Influencer Credibility has a positive and significant effect on Attitude Toward Influencers and Impulse Buying. Furthermore, Attitude Toward Influencers is found to have a significant direct effect on Impulse Buying. These findings confirm that influencer credibility not only directly stimulates impulse buying behavior but also indirectly influences it through the formation of positive consumer attitudes toward influencers. In conclusion, this study demonstrates that influencer credibility and consumer attitudes play critical roles in driving impulse buying in live streaming commerce. The findings contribute to the literature on digital marketing and consumer behavior by highlighting the importance of credible influencer communication. Practically, the results suggest that businesses and influencers should prioritize credibility-building strategies to enhance the effectiveness of live streaming marketing activities.